2006
DOI: 10.1007/s00198-006-0134-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a low-carbohydrate diet on bone turnover

Abstract: Although the patients on the low-carbohydrate diet did lose significantly more weight than the controls did, the diet did not increase bone turnover markers compared with controls at any time point. Further, there was no significant change in the bone turnover ratio compared with controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…The upper limit of the AMDR was set to mitigate against osteoporosis, kidney stones, and renal failure that might accompany chronically high protein intakes (45). Two small 12-wk intervention trials of high-protein diets in healthy adults showed either an adverse effect (46) or no effect (47) on markers of bone turnover or risk of nephrolithiasis, and other trials suggested beneficial effects of a high protein intake on bone health (48, 49). Observational studies in the general population did not find a relation between a high animal protein content in the diet and the development of renal stones (50, 51) and suggest that high-protein diets may only be detrimental in those with existing renal insufficiency (52).…”
Section: Discussionmentioning
confidence: 99%
“…The upper limit of the AMDR was set to mitigate against osteoporosis, kidney stones, and renal failure that might accompany chronically high protein intakes (45). Two small 12-wk intervention trials of high-protein diets in healthy adults showed either an adverse effect (46) or no effect (47) on markers of bone turnover or risk of nephrolithiasis, and other trials suggested beneficial effects of a high protein intake on bone health (48, 49). Observational studies in the general population did not find a relation between a high animal protein content in the diet and the development of renal stones (50, 51) and suggest that high-protein diets may only be detrimental in those with existing renal insufficiency (52).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst there are many studies on the effects of dietary protein levels on bone metabolism in humans the few investigations on ketogenic diet and bone metabolism were performed on epileptic children. But even if we assume a higher protein intake during a KD (and it is not completely correct as stated above) recently published articles suggested that there is not a negative effect on bone health [92,93,94,95]. …”
Section: It Is Safe For Obese Subjects?mentioning
confidence: 98%
“…Acting as a buffer system, bone aids in the modulation of acid-base homeostasis (8) through the release of calcium (9). In theory, elevated protein consumption is acidogenic (6), resulting in increased bone resorption (10). An observational study in women suggests that HP diets are associated with higher bone resorption (11), while 2 others suggest that HP diets of animal sources resulted in higher risk of fracture of the forearm (12) or hip fracture (13).…”
Section: Introductionmentioning
confidence: 97%